Otimização da síntese da estrutura zeólítica MCM-22 – Modificação dos parâmetros de síntese - Sampaio, Aline da Silva (2015)
MCM-22 is a typical representative of the MWW family zeolite being obtained from laminated precursor MCM-22 (P) after calcination process having high surface area and high thermal stability. In this work, we carried out an optimization of the synthesis process of MCM-22 zeolite, in order to reduce the amount of reactants used and the crystallization time. The zeolite was synthesized using three different sources of silicon (Aerosil silica, silica gel and Ultrasil 60) and static hydrothermal treatment; in order to evaluate the influence of silicon source on the formation of the structure and physicochemical properties. The syntheses were performed without aging and with aging at room temperature and at 40 ° C for each source of silicon. It was also a study on the influence of calcination on the formation of MCM-22 structure. The materials (MCM-22 (P) and MCM-22) were characterized by X-ray diffraction (XRD); textural analysis of nitrogen adsorption at low temperature; scanning electron microscopy (SEM); spectroscopy in the infrared (FT-IR); thermogravimetry / derivative thermogravimetry (TGA / DTG) and determination of acidity termoprogramada desorption of NH3 (NH3-TPD). The X-ray diffraction showed that the synthesis of the materials has been successful, with the characteristic peaks of the MWW topology. In the conditions proposed in this work it was possible to optimize the synthesis of MCM-22 zeolite, which is obtained in a short time of 4 days without aging, for the sources of silica and Aerosil Ultrasil, and 3-day aging at 40 ° C for source of Aerosil silica. Unable to the formation of MCM-22 zeolite with silica gel within 8 days. The X-ray diffraction confirmed the obtaining of MCM-22 with high purity and crystallinity without the presence of any contaminant phase in a short time (4 days) in the absence of aging. Through the analysis (FT-IR) was confirmed the presence of the intrinsic vibrations of TO4 tetrahedrons that provide internal and external bands characteristics of these materials. Through the thermogravimetric analysis (TGA / DTG) it was found that higher weight loss occurred between 180 and 530 ° C and corresponds to the output of most of the organic driver. The results of BET showed that the textural properties of MCM-22 zeolite were heavily dependent on silicon source and treatment of synthesis gel. Generally, the samples showed a surface area higher than 500 m2 / g. From acid analysis by NH3-TPD it was observed that acid sites present in the samples were predominantly mild and strong acid sites. The source of silicon and the aging of the gel did not influence the acidity of the material. The evaluation method of calcination showed that the form of calcination used to obtain MCM-22 influences the textural properties of the zeolite.